Respiratory training in an individual with amyotrophic lateral sclerosis. Issue 10 (1st September 2016) - Tabor, Lauren C.; Rosado, Karen M.; Robison, Raele; Hegland, Karen; Humbert, Ianessa A.; Plowman, Emily K.
Abstract: We examined the impact of expiratory muscle strength training on maximum expiratory pressure, cough spirometry, and disease progression in a 71‐year‐old male with amyotrophic lateral sclerosis. Maximum expiratory pressure declined 9% over an 8‐week sham training period, but subsequently improved by 102% following 8 weeks of expiratory muscle strength training. Improvements in cough spirometry and mitigated disease progression were also observed post expiratory muscle strength training. Improvements in maximum expiratory pressures were maintained 6 months following expiratory muscle strength training and were 79% higher than baseline data obtained 301 days prior. In this spinal‐onset amyotrophic lateral sclerosis patient, respiratory training improved subglottic air pressure generation and sequential cough generation.